2022
DOI: 10.1002/cnm.3590
|View full text |Cite
|
Sign up to set email alerts
|

Central femoral tunnel placement can reduce stress and strain around bone tunnels and graft more than anteromedial femoral tunnel in anterior cruciate ligament reconstruction

Abstract: The present study investigated the effects of anteromedial (AM) and central femoral footprint placement on stress and strain distribution around the femoral and tibial tunnel and graft following anterior cruciate ligament reconstruction (ACLR). A three‐dimensional (3D) reconstructed knee model was validated and used for simulating ACLR by finite element analysis. A combined loading during normal human walking was applied to the knee models using different anatomic femoral tunnel placement at 20° knee flexion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Repeated bone strains cause microscopic fatigue damage in bone with an operational threshold strain range greater than 3000 microstrain [ 6 ]. Researchers also used the strain around the bone tunnel to account for bone tunnel enlargement after ACL reconstruction in FE simulation [ 2 ]. The current results showed that the volume of cancellous bone strain within 1000–3000 microstrain increased as the tunnel flattened.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated bone strains cause microscopic fatigue damage in bone with an operational threshold strain range greater than 3000 microstrain [ 6 ]. Researchers also used the strain around the bone tunnel to account for bone tunnel enlargement after ACL reconstruction in FE simulation [ 2 ]. The current results showed that the volume of cancellous bone strain within 1000–3000 microstrain increased as the tunnel flattened.…”
Section: Discussionmentioning
confidence: 99%
“…Author details 1 Division of Orthopaedics and Traumatology, Department of Orthopaedics, Nanfang Hospital, Southern Medical University, Guangzhou, China. 2 The First Clinical College of Southern Medical University, Guangzhou, China. 3 Department of Orthopedic Surgery and Orthopedic Biomechanical Laboratory, Shanghai Jiao Tong University Affiliated Sixth People's Hospital, Shanghai, China.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Commonly used ACL grafts include autologous tendons such as the hamstring tendon and the patellar tendon, allogeneic tendons and artificial grafts ( Wang et al, 2020a ). Different positions, shapes and quantities of bone tunnels have also been used to achieve anatomic and non-anatomic reconstructions of the bone insertions ( Yao et al, 2012 ; Wang et al, 2020b ; Cheng et al, 2021 ; Cheng et al, 2022 ). Clinical outcomes have been reported to be good to excellent at 2 years post-surgery ( Komzak et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tunnel projects are facing more engineering challenges as the tunnels are becoming longer, bigger, deeper, and clustered these days [1][2][3][4][5][6][7][8][9]. Under the condition of high ground temperature, the stress on tunnel support structure and surrounding rock is even more complex under the multiple and simultaneous actions of temperature, stress, internal water pressure, and ground stress, etc.…”
Section: Introductionmentioning
confidence: 99%